2010
DOI: 10.1002/eji.201040895
|View full text |Cite
|
Sign up to set email alerts
|

The biology of myeloid‐derived suppressor cells: The blessing and the curse of morphological and functional heterogeneity

Abstract: Summary Myeloid-derived suppressor cells (MDSC) play an important role in the cellular network regulating immune responses in cancer, chronic infectious diseases, autoimmunity, and in other pathologic conditions. Morphological, phenotypic and functional heterogeneity is a hallmark of MDSC. This heterogeneity demonstrates the plasticity of this immune suppressive myeloid compartment, and shows how various tumors and infectious agents can have similar biological effects on myeloid cells despite the differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
497
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(508 citation statements)
references
References 55 publications
11
497
0
Order By: Relevance
“…88 MDSCs are classically distinguished between Monocytic (Mo-MDSCs) and Granulocytic (G-MDSCs) subsets based on morphological and phenotypical aspects. 88 Peripheral blood MDSC levels were higher in patients with ATC compared to healthy controls and correlated with the serum level of IL-10, thus suggesting a correlation between MDSCs and systemic immunosuppression. 89 The only study investigating the significance of TC-infiltrating MDSCs failed to find an association between MDSC density and patient survival.…”
Section: Mdscs: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…88 MDSCs are classically distinguished between Monocytic (Mo-MDSCs) and Granulocytic (G-MDSCs) subsets based on morphological and phenotypical aspects. 88 Peripheral blood MDSC levels were higher in patients with ATC compared to healthy controls and correlated with the serum level of IL-10, thus suggesting a correlation between MDSCs and systemic immunosuppression. 89 The only study investigating the significance of TC-infiltrating MDSCs failed to find an association between MDSC density and patient survival.…”
Section: Mdscs: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…MDSCs constitute one of the major populations of immune cells capable of regulating antitumor immune responses (40). In addi- (E-G) Six days after tumor challenge, tumors and TDLNs were collected and the expression of CD86 on DCs (defined as CD3 2 NKp46 2 B220 2 CD11c + ) was evaluated by flow cytometry (E), the relative abundance of IFN-b transcripts was evaluated by qPCR (F), and the frequency of DCs was evaluated by flow cytometry.…”
Section: Nk Cells Limit DC Maturation Without Affecting Other Regulatmentioning
confidence: 99%
“…Several factors have been involved into the generation and functionality of MDSCs, particularly arginase, Signal Transducer and Activator of Transcription 3 (STAT3), indoleamine 2,3-dioxygenase (IDO), reactive oxygen species and others. 18,19 As previous studies found that ECP enhances arginase I mRNA expression and enzyme activity in GvHD patients, 31 we focused on this pathway in our study. Our analyses demonstrated that ECP treatment increased arginase I activity both extracellularly in serum and intracellularly in the PMN-MDSC-containing PBMC fraction in GvHD patients, with PMN-MDSCs showing tendentially higher arginase I activity compared with autologous PBMCs (Figure 2c and Supplementary Figure 7).…”
Section: Neutrophilic Mdscs Functionally Suppress T-cell Responsesmentioning
confidence: 99%
“…17 Myeloid-derived suppressor cells (MDSCs) represent an innate immune cell population characterized by their capacity to potently suppress T-cell proliferation and T-cell cytokine responses. 18,19 Although MDSCs have been initially reported to have a role in cancer, an emerging body of evidence suggests that MDSCs are induced in a broad variety of chronic inflammatory disease conditions as an intrinsic anti-inflammatory mechanism induced to dampen excessive T-cell activities. 20 Functionally, MDSCs are comparable to Tregs, but can be characterized and isolated based on surface marker expression profiles.…”
Section: Introductionmentioning
confidence: 99%